Analysis of the Components of 236 Cases of Urinary Stones in Xinjiang Uyghur Children - Aierken, Yeerfan; Ye, Erdeng; Abudureyimu, Abudusaimi; Li, Shui-Xue; Kadier, Abudushataer; Keyoumu, Hanikezi; Liu, Dong (European Journal of Pediatric Surgery, 2022)
Introduction The aim of the study is to explore the relationship between clinical characteristics and urinary calculus in Xinjiang Uyghur children, and to provide clinical basis for the prevention as well as treatment of urinary stone.Materials and Methods In total, 236 urinary tract stone samples were collected from pediatric patients from February 2017 to April 2019, and those samples were analyzed by infrared spectroscopy. Stone compositions were compared with demographic data.Results Among the 236 cases, 166 cases were boys (70.34%) and 70 cases were girls (29.66%), with a male-to-female ratio of 2.37:1. A total of 21 kinds of calculi were detected, including 107 cases with six kinds of simple calculi and 129 cases with 15 kinds of mixed calculi. In this study, magnesium ammonium phosphate hexahydrate was only found in boys, and the difference was statistically significant (6.6 vs. 0.0%, p = 0.037). There were statistical differences in the age distribution of children with ammonium hydrogen urate, calcium oxalate, and other stone components (p < 0.05), while there were no statistical differences in the age distribution of children with apatite carbonate, magnesium ammonium phosphate hexahydrate, and anhydrous uric acid. The results showed that there was a significant difference in the localization of calculi between male and female children (upper urinary tract stones: 78.9 vs. 98.6%, p < 0.001).Conclusion Uyghur pediatric patients with urolithiasis were young and the majority of stones was mixed, The main components of calculi were ammonium hydrogen urate, calcium oxalate and apatite carbonate, and there are differences in the localization of calculi between genders.
Keywords: urinary tract stone; children; stone composition; Uyghur